2000
DOI: 10.1103/physrevc.62.044308
|View full text |Cite
|
Sign up to set email alerts
|

Lowest-order constrained variational calculation forβ-stable matter at finite temperature

Abstract: The method of lowest-order constrained variational, which predicts reasonably the nuclear matter semi-empirical data is used to calculate the equation of state of beta-stable matter at finite temperature. The Reid soft-core with and without the N-∆ interactions which fits the N-N scattering data as well as the U V 14 potential plus the three-nucleon interaction are considered in the nuclear many-body Hamiltonian. The electron and muon are treated relativistically in the total Hamiltonian at given temperature, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…[9][10][11][12] In these calculations, a very good agreement was found between the LOCV results and the more complicated approaches such as the DMC and the FHNC, which go beyond the lowest order. 13 14 It has been also shown that the LOCV formalism has very good convergence properties i.e., the three-body cluster energy is much smaller than the two-body one.…”
Section: Introductionsupporting
confidence: 53%
“…[9][10][11][12] In these calculations, a very good agreement was found between the LOCV results and the more complicated approaches such as the DMC and the FHNC, which go beyond the lowest order. 13 14 It has been also shown that the LOCV formalism has very good convergence properties i.e., the three-body cluster energy is much smaller than the two-body one.…”
Section: Introductionsupporting
confidence: 53%
“…This method was reformulated to include more sophisticated interactions [34], such as UV 14 , AV 18 [35], and charge-dependent Reid potential (Reid93) [36]. The LOCV method has been also developed for calculating the various thermodynamic properties of hot and frozen homogeneous fermionic fluids, such as symmetric and asymmetric nuclear matter [37], β-stable matter [38], helium-3 [39], and electron fluid [40], with different realistic interactions. Recently, the LOCV formalism was developed for covering the relativistic Hamiltonian with a potential that has been fitted relativistically to nucleon-nucleon phase shifts [41].…”
Section: The Variational Methodsmentioning
confidence: 99%
“…The LOCV formalism has been also extended for calculating the various thermodynamic properties of the symmetric nuclear matter [28], neutron matter [29], β-stable matter [30] and the asymmetrical nuclear matter [31] with the Reid and -Reid potentials. In the above calculations the liquid-gas phase transition, corresponding critical temperatures and various critical index have been found.…”
Section: Introductionmentioning
confidence: 99%